Are soccer players born later in the year more technically skilled than those born earlier in the year - Hunter, A. H.; Smith, N. M. A.; Camata, T. V.; Crowther, M. S.; Mather, A.; Moura, F. A.; Santiago, P. R. P.; Wilson, R. S. (International Journal of Sports Science & Coaching, 2023)
In many youth sports, selection into elite training academies is dominated by athletes born earlier in the year. Previous research suggests this is partly due to these athletes being more physically developed than their younger peers. How athletes born later in the year survive in elite academies is less understood. Here, we tested the hypothesis that players born later in the year are more technically skilled than their peers born earlier in the same year. Using 150 youth players (10-19 years of age) from an elite Brazilian soccer academy, we measured each player's date of birth, height, and mass; sprinting ability; dribbling ability; and kicking accuracy and speed. We found most players in this academy were born in the first half of the year, and those born earlier in the year (relatively older) tended to be taller and heavier than those born later in the same year (relatively younger). In addition, relatively older players were faster when sprinting and dribbling the ball in a straight line. Conversely, relatively younger players were more accurate when passing the ball with their nondominant foot, providing some evidence these players were more technically skilled than their older peers of the same age. We suggest skill tests with youth players need to consider relative age and physical size in order to best assess a player's potential.